INTERVENE‐HF: feasibility study of individualized, risk stratification‐based, medication intervention in patients with heart failure with reduced ejection fraction. (1st February 2021) - Zile, Michael R.; Costanzo, Maria Rosa R.; Ippolito, Ekaterina M.; Zhang, Yan; Stapleton, Russell; Sadhu, Ashish; Jimenez, Javier; Hobbs, Joe; Sharma, Vinod; Warman, Eduardo N.; Streeter, Lindsay; Butler, Javed
Abstract: Aims: Determine the feasibility of implementing a heart failure (HF) management strategy that (i) uses a device‐based, remote, dynamic, multimetric risk stratification model to predict the risk of HF events and (ii) uses a standardized, centrally administered, ambulatory medication intervention protocol to reproducibly and safely decrease elevated risk scores. Methods and results: Prospective, non‐randomized, single‐arm, multicenter feasibility study (Intervene‐HF) was conducted in HF patients implanted with a cardiac resynchronization therapy with implantable cardio defibrillator (CRT‐D) with TriageHF risk score feature. Certified HF nurses (CHFN) in the Medtronic Care Management Services Program implemented an ambulatory medication intervention strategy by following a standardized guided action pathway triggered by risk‐based alert. When CHFN received notification of increased risk score (HF care alert), they implemented a 3 day course of diuretic up‐titration (PRN) previously prescribed by a physician. Safety was monitored daily. Recovery after PRN was defined as ≥70% recovery of impedance toward baseline levels. Sixty‐six patients followed for 8.2 ± 3.9 months had 49 HF care alerts. Twenty‐three of 49 alerts did not receive PRN due to protocol‐mandated criteria. Twenty‐six of 49 alerts received PRN, 22 were completed, and 19 led to impedance recovery. Four interventions were stopped for safety without leading to an adverse event (AE). One of 26 PRNs was followed by a HF event. Eighty‐five per cent (22/26) of PRNs were completed without an AE; 69% (18/26) met the recovery criteria. Conclusions: The Intervene‐HF study supports the feasibility of testing, in a large randomized clinical trial, an ambulatory medication intervention strategy that is physician‐directed, CHFN‐implemented, and based on individualized device risk stratification.